Quantitative and qualitative assessment of pine seedlings under controlled undergrowth disturbance: Fire and soil scarification - Przybylski, Paweł; Jastrzȩbowski, Szymon; Ukalski, Krzysztof; Tyburski, Łukasz; Konatowska, Monika (Frontiers in Forests and Global Change, 2022)
Scots pine (Pinus sylvestris L.) is the most widespread forest tree species in Central Europe. The range of Scots pine depends on the influence of forest management on stand species composition, as the potential for the natural regeneration of Scots pine monocultures is smaller than the current range of the species. To achieve regeneration, pine requires specific ecological conditions, including adequate soil preparation. The literature notes that the effective natural regeneration of pine requires fire or mixing the organic soil layer with the mineral layer. This hypothesis was critically evaluated carrying out work with the main objective of comparing the germination and growth dynamic of pine seedlings in two variants, simulating fire or soil scarification against natural conditions. The research focused on analyzing the growth of pine seedlings from germination to the final number of seedlings, which remained unchanged until the end of the experiment. The evaluation was carried out in soil monoliths from Kampinos National Park (KNP), in which seeds from a homogeneous mother stand were planted. The quantitative and qualitative characteristics of the seedlings were statistically evaluated, including analyses of their root system characteristics. The results confirmed the positive effect of mixing an organic and mineral layer at the germination stage and during the subsequent growth of the pine. The seedlings had a high survival rate (65.3%). However, the positive effect of fire on the regenerative capacity of pine could not be confirmed; the number of obtained seedlings (29.5%) was significantly lower than in the control variant. In addition, the “fire variant” was characterized by high seedling mortality immediately after germination. Root systems were important for the survival of the seedlings, the development of which was affected by the tested variant. The analyses performed may have implications for the development of research on the possible natural regeneration of Pines after natural disturbances. Additional topic that needs further research is the response of seedling root systems to changes in soil conditions.